A Cross-sectional Analysis of the Characteristics of Individuals With Parkinson Disease Who Avoid Activities and Participation Due to Fear of Falling. Issue 1 (January 2017) - Landers, Merrill R.; Lopker, Morgan; Newman, Molly; Gourlie, Russell; Sorensen, Spencer; Vong, Rithea
Abstract : Background and Purpose: Avoidance behavior can have deleterious consequences on health and quality of life for persons with Parkinson disease (PD); for this reason, it is important to identify potentially mitigable characteristics. We compared the characteristics of individuals with PD who exhibit fear of falling (FOF) avoidance behavior with those who do not. Methods: Fifty-nine participants with PD were classified as avoiders (n = 27) or nonavoiders (n = 32) by using the Fear of Falling Avoidance Behavior Questionnaire and compared across 5 domains: demographic characteristics; PD-specific symptoms (subtype, Movement Disorder Society–Unified Parkinson's Disease Rating Scale [MDS-UPDRS], Hoehn and Yahr Scale, Parkinson's Disease Questionnaire–39 [PDQ-39]); balance and falls (fall history, Berg Balance Scale [BBS], Activities-Specific Balance Confidence [ABC] Scale, Impact of Events Scale, Consequences of Falling Questionnaire [CoFQ]); physical performance (30 Second Sit-to-Stand Test, Timed Up and Go Test, physical activity monitoring); and psychological factors (Zung Anxiety Scale, Beck Depression Inventory [BDI]). Results: There were no differences between avoiders and nonavoiders for demographic characteristics and fall history ( P s > 0.272). Avoiders had worse MDS-UPDRS ( P s < 0.014) and PDQ-39 scores ( P s < 0.028). Avoiders had poorer balance performance (BBS, P = 0.003), lower balance confidence (ABC, P < 0.001), and more fall catastrophization (CoFQ, P < 0.001). Avoiders reported more depression ( P = 0.015) and anxiety ( P = 0.028). Discussion and Conclusions: PD FOF avoiders had more involved symptoms and scored lower on balance and physical performance measures. In addition, they reported greater psychological stress. Several potentially mitigable characteristics of those with FOF avoidance behavior were identified. Video Abstract available for more insights from the authors (see Supplemental Digital Content 1, available at:http://links.lww.com/JNPT/A153 ). Abstract : Supplemental Digital Content is Available in the Text.